Native English or Singlish? : the relative influences of language ideals and communicative situations on language-related behavioural intentions. - Trinh, Lien Huong. (2012)
Based on Kachru’s Three Circle Model on the spread of English in different parts of the world, I question how foreign university students migrating from Expanding Circle countries to Singapore deal with the “clash” of linguistic norms set by different circles. This research hence explores English speaking behavioural intentions of these foreign tertiary students in Singapore and how they account for their language behavioural plans. The collected data reveal that most students held a notion on the native English-Singlish dichotomy, seeing native English as standard and superior while regarding Singlish as improper and non-standard. Considering language behavioural intentions, most respondents claimed to adopt three main strategies: speech maintenance, adapting to the formality level of the communicative situation, and speech convergence. Looking into respondents’ accounts for these intended strategies, I argue that speakers orient their language use not only towards language perceptions but also the communicative situations they are in. However, the relative influences of these two factors on language use vary among different cases.